Teachers’ Responsibilities in Accommodate Parents to Improve Students’ Academic Attainment - Ramalingam, Shanti; Balakrishnan, Rukmani Devi; Machappan, Kalidass (Advances in Social Sciences Research Journal, 2022)
The objective of this research is to identify the teachers’ responsibilities in helping parents to improve students’ academic attainment. This research will focus on how the school manage the teachers’ responsibilities within these four main aspects, i.e., parenthood, communication, home schooling and volunteerism which can help to increase students’ academic development. One hundred of Year 6 students at West Country Barat Primary School became the sample of this research and a set of questionnaires were used as the instrument. All the data were processed by using SPSS software to identify the mean score, frequency percentage, Pearson Correlation and One Way ANOVA. The findings of the research indicated a positive significant relationship between the direct roles of teachers and also school management in assisting parents to improve students’ academic achievement in the aspect of volunteerism. Several suggestions were also made to improve teachers’ responsibilities and school management in assisting parents to improve students’ academic achievement in the aspects of communication, parenthood and home schooling.